Sodium Intake and Related Diseases (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
It has been recognized that moderation in the use of salt (sodium chloride) prevents the tendency of blood pressure to increase with age. On the other hand, the abuse of salt frequently leads to increases in blood pressure and contributes to the development of hypertension, particularly in overweight or obese people, in people with diabetes, in the elderly, and in genetically predisposed subjects. This Special Issue aims to provide a better understanding of the relationship between sodium intake and related diseases, in particular: (i) the effect on health status and description of the biochemical processes involved; and (ii) the use of salt and related risks. The main topics are studies in the management and treatment of sodium-intake-related diseases, epidemiological studies of the relationship between salt intake and related diseases, focuses on the mechanism of action; delineation of the mechanisms of action, and in vitro and in vivo studies.